Komite Audit Sebagai Pemoderasi Pengaruh Workload dan Masa Perikatan Audit Pada Kualitas Audite - Rusli, Theresia Julina; Wiratmaja, I Dewa Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis, 2016)
This  research  aims to find empirical evidence  about the impact  of  workload  and  audit tenure  on  audit quality  and  using audit  committee  as  a  moderating  variable. This  research  focused  on  manufacturing companies  that  listed  on  the  Indonesia Stock Exchange. Sample was collected using   purposive sampling method and resulted 31  companies as a final sample.  The  data are analyzed by using Moderated Regression Analysis (MRA). The results of  this research indicate  that the  workload  has a negative  impact on  audit quality.  Audit tenure has a positive impact on audit quality. Audit committee reduces the negative impact of workload on audit quality. And audit committee reduces the positive impact of audit tenure on audit quality. Keywords: Workload, audit tenure, audit committee, audit quality
Keywords: Workload, Audit Tenure, Audit Committee, Audit Quality